The effect of the Covid-19 pandemic on the stock market reaction to companies in the Consumer Goods Industry sector on the Indonesia Stock Exchange - Purnama, Muhamad Fadia Adika; Pratiwi, Lovianda; Azemy, Robby; Nugraha, Vanesa Berliani; sari, Yunnita; Brata, Ignatius Oki Dewa (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study discusses whether there are differences in stock prices in consumer goods sector companies before and after the Covid19 pandemic. This is done whether there is a significant shock in this industry during the pandemic. In Indonesia the first case of COVID-19 was announced by the government on March 2, 2020. With the Covid-19 starting to spread, the government urges the public to stay at home, isolate themselves and reduce gathering activities or maintain distance and enforce the Government Policy, namely social restrictions on a scale large (PSBB). With the appeal and the enactment of the PSBB, it has an impact on many sectors of people's lives, especially in the economic sector. The test was carried out with a sample of 56 companies listed on the Indonesia Stock Exchange, which from 2019 to 2020 were active on the Exchange. Hypothesis testing uses the T test or different tests to see how significant the shocks that occur in the industry are. The test results prove that from the existing financial report data and accounting records, it can be concluded that there is no significant change to the consumer goods sector industry, this is because government policies during the pandemic have actually made this industry sustainable.